Peningkatan Kompetensi Pengelola Bumdes Melalui Pelatihan Pembukuan Dan Keuangan Bumdes Di Kekelengen Desa Sugihen - Karo Karo, Sastra; Ginting, Hartono; Manurung, John Sihar; Ginting, Jasa (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2024)
Village-owned enterprises (BUMDes) are a government effort to empower rural communities. BUMDes was formed to become a driving force for the village economy and a source of village income. BUMDes that are managed professionally will support the realization of predetermined goals and objectives, including financial management. Problems arise due to the limited human resources of BUMDes managers. Problems arise due to the limited human resources of BUMDes managers. Socialization and training are essential so BUMDes Kekelengen Sugihen village can develop well. The strengths of BUMDes Kekelengen are that it has very fertile agricultural land, the village population is 241 heads of families, it has full support from the government, from the village to the central government, it has sufficient water sources for village needs, the economy of the Karo district and National is quite good, and the distance is quite close to the cities of Berastagi and Medan. Meanwhile, the Weaknesses are that human resources (management) lack motivation and focus and are still limited; management and admin staff are still less competent in several fields, specially making financial reports, and Office equipment is still available in the village office. If we look at opportunities, many business opportunities can still be explored, such as savings and loan cooperatives, agricultural equipment shops, and basic needs shops. Exploring the potential of villages to become agrotourism villages, as threats (Threats) are village entrepreneurs who are already active or going first, entry of entrepreneurs from outside the village, and rapid development. BUMDes financial reports should be the same as other institutions; they must be presented and managed professionally, transparently, accountable, systematically, and completely, but BUMDes Kekelengen Sugihen Village only records cash in and cash out using a manual process. Complete and systematic financial reports will be attractive to stakeholders. This service produces output in the form of an EFA (Excel For Accounting) template and the delivery of a computer that has been installed with Accurate, which can be used for bookkeeping and financial reporting for BUMDes Kekelengen, Sugihen village